Two new species of nasal mites of the genus Ptilonyssus (Rhinonyssidae) from sparrows from the Leningrad province, Russia - DIMOV, I.; MIRONOV, S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Two new nasal mites of the genus Ptilonyssus Berlese and Trouessart, 1889 are described from sparrows of the genus Passer (Passeriformes: Ploceidae) found in the Leningrad province, Russia: Ptilonyssus degtiarevae, n. sp. from Passer domesticus (L.) and Ptilonyssus lovottiae n. sp. from Passer montanus (L.). Ptilonyssus degtiarevae, n. sp. belongs to the newly established orthonychus species complex, and Ptilonyssus lovottiae n. sp. is referred to the hirsti species complex. The species content of the hirsti complex0, originally defined by Fain and Bafort 1963 is enlarged comparing to the concept of previous researchers.